A dynamic system for delivering controlled bromine and chlorine vapor exposures to weanling swine skin. (June 2014) - Snider, Thomas H.; Perry, Mark R.; Richter, William R.; Plahovinsak, Jennifer L.; Rogers, James; Reid, Frances M.; Graham, John S.
Abstract Context: Assessing the hazards of accidental exposure to toxic industrial chemical (TIC) vapors and evaluating therapeutic compounds or treatment regimens require the development of appropriate animal models. Objective: The objective of this project was to develop an exposure system for delivering controlled vapor concentrations of TICs to the skin of anesthetized weanling pigs. Injury levels targeted for study were superficial dermal (SD) and deep dermal (DD) skin lesions as defined histopathologically. Materials and methods: The exposure system was capable of simultaneously delivering chlorine or bromine vapor to four, 3-cm diameter exposure cups placed over skin between the axillary and inguinal areas of the ventral abdomen. Vapor concentrations were generated by mixing saturated bromine or chlorine vapor with either dried dilution air or nitrogen. Results: Bromine exposure concentrations ranged from 6.5 × 10−4 to 1.03 g/L, and exposure durations ranged from 1 to 45 min. A 7-min skin exposure to bromine vapors at 0.59 g/L was sufficient to produce SD injuries, while a 17-min exposure produced a DD injury. Chlorine exposure concentrations ranged from 1.0 to 2.9 g/L (saturated vapor concentration) for exposures ranging from 3 to 90 min. Saturated chlorine vapor challenges for up to 30 min did not induce significant dermal injuries, whereas saturated chlorine vapor with wetted material on the skin surface for 30–60 min induced SD injuries. DD chlorine injuries could not be induced with this system. Conclusion: The vapor exposure system described in this study provides a means for safely regulating, quantifying and delivering TIC vapors to the skin of weanling swine as a model to evaluate therapeutic treatments.